Evaluation of Infrastructure and Cybersecurity in Supporting the Digital Transformation of Public Services in Tangerang City - Kosasih, Achmad; Aditya, Toddy; Ramadhan, Sukma Aditya (Jurnal Manajemen Pelayanan Publik, 2025)
This research aims to evaluate the readiness of digital infrastructure and cybersecurity in supporting the digital transformation of public services in Tangerang City, especially the Tangerang LIVE application. The application is designed to integrate various public services in one digital platform, but data shows a decline in the use of features by the public. This study uses a quantitative approach with Structural Equation Modeling (SEM) to test the relationship between digital infrastructure, cybersecurity, and digital public services. The results of the study show that cybersecurity has a greater influence in building public trust in digital public service applications compared to digital infrastructure. While digital infrastructure is important to support accessibility and efficiency, security factors including awareness, system readiness, and threat resilience play a greater role in ensuring sustainability and user trust. Therefore, the simultaneous strengthening of these two factors is critical to ensuring the successful digital transformation of safe, efficient, and reliable public services